2001
DOI: 10.1385/bter:83:3:191
|View full text |Cite
|
Sign up to set email alerts
|

Transport Measurements Across Caco-2 Monolayers of Different Organic and Inorganic Selenium: Influence of Sulfur Compounds

Abstract: The transport and uptake of the most common Se compounds, selenate (SeO42-), selenite (SeO3(2-)), selenomethionine, and selenocystine, were investigated using confluent monolayers of Caco-2 cells, a human carcinoma cell line. Comparative measurements were performed in the absorptive (apical to basolateral side) and exsorptive (basolateral to apical side) directions. Apparent permeability coefficients (Papp), calculated from transport experiments in the absorptive direction, showed increasing values in the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
7
13
0
Order By: Relevance
“…Considering that the R163C RyR1 mutation in skeletal muscle resulted in a significantly increased cytosolic Ca 2ϩ (about 2-fold of the normal resting concentration, this study and that by Yang et al (30), an activation of several calcium-dependent pathways was expected leading to the activation of a slow-twitch fiber program to increase the resistance to fatigue, the oxidative capacity, and the calcium buffering capacity of mitochondria. The values for total calcium contents of WT mitochondria evaluated in this study were within the range of those previously reported for rodent skeletal muscle using ICP-MS or other techniques (82)(83)(84)(85)(86). The significantly higher concentrations of mitochondrial calcium content in R163C reported here may stem from the chronically elevated (2-4-fold) resting intracellular Ca 2ϩ concentrations in intact MHS skeletal muscle from various species (76 -78).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Considering that the R163C RyR1 mutation in skeletal muscle resulted in a significantly increased cytosolic Ca 2ϩ (about 2-fold of the normal resting concentration, this study and that by Yang et al (30), an activation of several calcium-dependent pathways was expected leading to the activation of a slow-twitch fiber program to increase the resistance to fatigue, the oxidative capacity, and the calcium buffering capacity of mitochondria. The values for total calcium contents of WT mitochondria evaluated in this study were within the range of those previously reported for rodent skeletal muscle using ICP-MS or other techniques (82)(83)(84)(85)(86). The significantly higher concentrations of mitochondrial calcium content in R163C reported here may stem from the chronically elevated (2-4-fold) resting intracellular Ca 2ϩ concentrations in intact MHS skeletal muscle from various species (76 -78).…”
Section: Discussionsupporting
confidence: 84%
“…Given that exposure of mitochondria to a sustained higher calcium concentration may lead to higher calcium uptake and net calcium accumulation, dissipation of the electrochemical gradient, decreased ATP production, and/or organelle swelling or bursting (79 -81), the calcium concentrations in mitochondrial and PM fractions were evaluated in WT and R163C skeletal muscle by ICP-MS. The values for total calcium contents of WT were within those reported for rodent skeletal muscle using ICP-MS or other techniques (690 -1500 nmol/g muscle wet weight) (82)(83)(84)(85)(86). Skeletal muscle mitochondria from R163C mice had 5.7 times more Ca 2ϩ than WT, and the Ca 2ϩ concentration in the cytosolic fraction was 1.8-fold higher than WT (Table 4).…”
Section: Higher Mitochondrial Calcium In Ryr1 R163c Skeletal Muscle Isupporting
confidence: 73%
“…The Se amounts were quantified by atomic absorption spectrometry. Only the selenoamino acids, SeMet and (SeCys) 2 , showed a net absorptive flux across the Caco-2 cell monolayer, suggesting that a transporter-mediated transcellular pathway was involved, while a paracellular pathway for selenate was suggested [15]. The Caco-2 cell model was in another study used to assess the production of the selenoprotein, glutathione peroxidase (GPx), from Semethylselenocysteine (MeSeCys), SeMet or selenite applied in concentrations between 15.6 and 125 nM Se, in time intervals between 8 and 72 h. GPx activity was determined by an enzyme assay while total Se was determined by AAS [16].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, absorptive flux describes the transport from the intestinal lumen to the serosal side, while exsorptive flux describes transport in the opposite direction. A thorough investigation on selenium permeability across filter grown Caco-2 cell monolayers was performed by Leblondel et al [15] who compared the permeabilities of the four seleno compounds (10 μM) selenite, selenate, SeMet, and selenocysteine (SeCys) 2 in the absorptive as well as exsorptive directions. The Se amounts were quantified by atomic absorption spectrometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation